Metodologia de avaliação das condições de funcionamento dos motores de indução trifásicos sob o enfoque da eficiência energética - Chiovatto, Ciciane (2011)
This thesis presents a methodology developed to obtain the characterist ic curves of threephase induction motors, in order to make it possible to diagnose the operating conditions of motors already installed in the industry. To execute the presented method it is needed data provided in the catalogs of motor manufacturers, as well as field measurements. The performance curves to be obtained are those of current, power factor and efficiency. The focus of this study is to analyze the motor s loading condition and attest if it is either oversized or not. The efficiency and power factor can be obtained through the loading, and the feasibility of swapping of the motor by another of an appropriate size is evaluated. The aim of this procedure is to increase the energy efficiency of the overall system.